Satellite Tracking System - Hamdi, Akmal Fariz; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2024)
The satellite monitoring system was developed to address the challenges associated with monitoring satellites and movements in real-time. The satellite tracking system continuously gathered information about the location and movement of the satellites. This data was then transmitted to a computer for processing and analysis. Users could access the information through a smartphone or computer web-based interface, providing them with real-time updates on satellite positions. The main objectives of the project were to create a real-time satellite tracking system that enabled users to easily monitor the movement of satellites, analyze the collected data, and display it in the user interface. The project utilises two stepper motors, two limit switches, an LCD display and an Arduino ESP32 board. The system operated based on the data received from satellite signals, utilizing it to predict the movement of the satellite using TLE (Two-line element) data sets and providing outputs to the user via Internet connectivity. The results of this project demonstrate the successful development of a fully functioning device capable of tracking the movement of a selected satellite as it passes overhead. The LCD display showcases the satellite being tracked, along with the time it will orbit overhead, and the values of azimuth, elevation, latitude, and longitude for the selected satellite. Additionally, a user-friendly web interface features buttons for selecting satellites to track. Google Sheets was employed to display satellite data and the location of the currently selected satellite on a map. Following this, a comparison was made between the project’s data and information from a specialized astronomical web page, In-The-Sky.org. ISS-ZARYA was tracked, resulting in latitude and longitude values of 32.63˚N and 105.27˚E. In contrast, In-The-Sky.org reported latitude and longitude values of 32.7˚N and 105.6˚E, respectively. Upon comparison, it was found that both the latitude and longitude values from the project and the In-The-Sky webpage were identical.